Investigation of the radiative decay \(b → s γ\) in the 3-4-1-1 model - Nguyen Tuan, Duy; Do Thi, Huong (Communications in Physics, 2023)
We investigate the branching ratio of the radiative decay \(b→ s γ\) in the 3-4-1-1 model with arbitrary charge parameters \(p,q\). We show that the new Higgs bosons, \(H_1^±\), and the new gauge bosons \(W_13,14 ^± p,q, Z_2,3\) contribute to this decay. Of these sources, the main contribution comes from the interaction of the singly-charged Higgs boson. If the spontaneous breaking of the enlarged gauge group symmetry down to the electroweak group is around a few TeVs, the predictions for the branching ratio Br\((b→ s γ)\) and meson mixing are both consistent with experimental constraints.